Evidence in Practice of Tissue Healing with Latex Biomembrane: Integrative Review - Suélia de Siqueira Rodrigues Fleury Rosa; Mário Fabrício Fleury Rosa; Marcos Augusto Moutinho Fonseca; Glécia Virgolino da Silva Luz; Carlos Federico Domínguez Avila; Aldira Guimarães Duarte Domínguez; Aldene Guimarães Duarte Dantas; Von Braun Richter (Journal of Diabetes Research)
Wound healing is a perfectly coordinated cascade of cellular, molecular, and biochemical events which interact in tissue reconstitution. Chronic diseases such as pressure ulcers (PU) and diabetes mellitus (DM) are considered risk factors for wound healing. Patients with such diseases often have higher sepsis, infection, and complication rates, since they have revascularization inhibition and low growth factor expression. Thus, latex biomembrane (LBM), a biocompatible material, derived from the latex of the rubber tree (Hevea brasiliensis) appears to create tendencies as an angiogenic-inducing tissue healing agent and as biomaterial, resulting from its structural qualities and its low cost when compared to conventional treatments. Therefore, this work aims at summarizing the results, experiments, and scientific findings that certify or recommend the use of LBM as a new technique to be applied effectively in the treatment of wounds. An integrative review was held in the BIREME, LILACS, Burns, MEDLINE, PubMed, and SciELO databases, from 2000 to 2016, using the following descriptors: “healing,” “diabetes mellitus,” “wounds,” and “latex membrane.” As a result, 600 experiments (out of 612) presented satisfactory results; however, 33% of the cases received explicit recommendations, 11% required more studies on the subjects, and 1% was denied. On the other hand, half of the studies did not expressly endorse its use, despite presenting satisfactory results. The LBM was characterized as a good therapeutic alternative in cases of wounds, including chronic diseases, such as diabetes mellitus and PU, due to its relevant potential for wound healing stimulation, acceleration of cell tissue mending and revascularization, or the reestablishment of angiogenic functions (creation of new blood vessels). The LBM was also confirmed to be safe as a biocompatible material whose structural qualities (elasticity, adaptability, impermeability, and possibility of suture), devoid of toxicity, allowed interaction between tissues and presented no hypersensitivity inducer and no antimicrobial effect.